Clinical implications of hepatitis A virus ribonucleic acid detection and genotyping in acute liver failure in children in Argentina - Sasbón, Jorge (2010)
Fil: Sasbón, Jorge S. Hospital de Pediatría Dr. Juan P. Garrahan. Unidad de Trasplante de Hígado y Cuidados Intensivos; Argentina.